2012
DOI: 10.1177/0149206312439327
|View full text |Cite
|
Sign up to set email alerts
|

At What Level (and in Whom) We Trust

Abstract: Despite the importance of trust across multiple levels in organizations, extant reviews have focused predominantly on trust at the individual level. A systematic review of trust research across levels and trust referents is sorely needed to synthesize the growing number of both micro and macro studies on this topic. Moreover, as trust is a linchpin for divergent areas, such as negotiation, leadership, team processes, human resource management, organizational change, entrepreneurship, and strategic alliances, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
251
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 617 publications
(266 citation statements)
references
References 463 publications
(679 reference statements)
4
251
0
11
Order By: Relevance
“…As interdependence and interactions with other team members are core elements of a virtual team member's job, the team member's level of trust toward those team members should impact on her or his level of job satisfaction. This is in line with a number of empirical findings (see Fulmer & Gelfand, 2012, for a review). As an example, McNall and Roch (2009) found that trust in the manager was significantly positively related to job satisfaction as employees who trust their supervisors are willing to reciprocate this trust in the form of desired work behaviors.…”
Section: Trust As Mediator Of the Relationship Between Social Comparisupporting
confidence: 92%
See 2 more Smart Citations
“…As interdependence and interactions with other team members are core elements of a virtual team member's job, the team member's level of trust toward those team members should impact on her or his level of job satisfaction. This is in line with a number of empirical findings (see Fulmer & Gelfand, 2012, for a review). As an example, McNall and Roch (2009) found that trust in the manager was significantly positively related to job satisfaction as employees who trust their supervisors are willing to reciprocate this trust in the form of desired work behaviors.…”
Section: Trust As Mediator Of the Relationship Between Social Comparisupporting
confidence: 92%
“…Employees are able to distinguish between different trust foci, that is, trusting the organization, the top management, their direct supervisor, or other members of their team (Fulmer & Gelfand, 2012). In this article we concentrate on the level of trust an individual in a virtual team holds toward her or his fellow team members.…”
Section: The Link Between Social Comparison and Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Research attests to the benefits of high employee trust. Trusting employees are more committed and stay with the organization longer, work harder and more cooperatively, share knowledge, and problem solve more effectively (e.g., Coyle‐Shapiro, Morrow, Richardson, & Dunn, ; Fulmer & Gelfand, ; Tremblay, Cloutier, Simard, Chenevert, & Vandenberghe, ; Whitener, ). In addition, trust in the employer enhances the effectiveness of high‐performance work practices by moderating the effects of these HR practices on justice perceptions and feelings of commitment (Alfes, Shantz, & Truss, ).…”
mentioning
confidence: 99%
“…Here, we distinguish employees’ interpersonal trust from their trust in the organization, and extend the examination of the role of control to employees’ trust in their employing organization. This responds to calls for greater specificity in the referent of trust (Fulmer & Gelfand, ) and theoretical work arguing that the assumptions for interpersonal trust are not always readily transferable to trust in the organization (Gillespie & Dietz, , p. 142). Trusting an organization entails different types of vulnerabilities, dependencies, and risks than trusting a person.…”
mentioning
confidence: 99%